Articulate Storyline chemistry learning with socio-scientific issues to enhance students' critical thinking - Khadijah, Siti; Sholahuddin, Arif; Nora’in, Miranda; Humaira, Norsifa; Rosita, Febry; Rezani, Muhammad Ismi (Universitas Negeri Yogyakarta, 2025)
Critical thinking is essential for students’ academic and life success, yet many students perform poorly because instructional approaches often fail to promote higher-order thinking. This study developed an interactive learning medium that integrates Socio-Scientific Issues (SSI) using Articulate Storyline and evaluated its validity, practicality, and effectiveness in improving students’ critical thinking about chemical bonding. The research employed a Research and Development (R&D) design based on the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Participants were 67 eleventh-grade students (34 from XI-1 and 33 from XI-4), aged 15–16 years. Data were collected using validation sheets, questionnaires, observation sheets, and pretest–posttest critical thinking tests. Results showed the media was valid (content validity index = 0.97), highly practical (mean practicality score = 4.33), and effective (mean N-gain = 0.77), indicating substantial improvement in students’ critical thinking. The study concludes that SSI-based interactive materials developed with Articulate Storyline are feasible and effective for teaching chemical bonding; theoretically, the findings support the role of SSI and digital interactive media in fostering higher-order thinking, and practically, teachers are recommended to adopt these materials to enhance critical-thinking instruction.